Normativity and Ontology of Law in Early Greek Philosophy - Goździalski, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The paper is devoted to the issues of the emergence of European science and philosophy, founded by the ancient Greeks. In the period known as the First Enlightenment, there was, on the one hand, a gradual departure from the mythological explanations of the reality, and, on the other, the construction of a new way of looking at the world, known as the study of nature. The inquiries of the ancient Greeks had an ontological dimension; they consisted in searching for the arche of the world and they were looking for the ultimate structure of reality, and, what is important, the human being was situated in these studies as an integral, but not the most important part of the Cosmos, subject to its laws. Presocratics did not put the human being above nature, because they did not strictly distinguish between the laws of nature and the laws of community. This was one of the reasons why the science of law did not arise at that time. Besides, the Greeks never reduced their right to the system, because too often gods or demos ‘interfered’ with the laws of the polis. It was a typical example of “law without jurisprudence”, because it was flexible and had vaguely formulated rules and institutions. Another significant factor here was the lack of the trained group of professional lawyers. This period ended with the advent of Socrates’ philosophy. Up to his time, philosophy had studied numbers and movements, and had dealt with the question of where all things have their origin and where they disappear; it also had observed the stars, the distances between them, their circuits, as well as had studied phenomena which appear in the sky. The early sages believed that they could gain knowledge by conducting research into natural phenomena themselves. Socrates rejected the ontology and study of nature initiated by the Milesians and other early Greek thinkers in favour of searching for the meaning of words and concepts found in the Athenian polis language. He believed that finding the meaning of words translated into revealing the reality which could not be reached otherwise.